Dangerous trade : histories of industrial hazard across a globalizing world - Sellers, Christopher C.; Melling, Joseph (Temple University Press, 2012)
From anthrax to asbestos to pesticides, industrial toxins and pollutants have troubled the world for the past century and longer. Environmental hazards from industry remain one of the world's foremost killers.Dangerous Trade establishes historical groundwork for a better understanding of how and why these hazards continue to threaten our shrinking world.In this timely collection, an international group of scholars casts a rigorous eye towards efforts to combat these ailments. Dangerous Trade contains a wide range of case studies that illuminate transnational mov.